Production of Pha (poly hydroxy alkanoates) by Ralstonia eutropha on hydrolysed sago starch as main substrate using fed-batch cultivation method - Syamsu, Khaswar; M. Fauzi, Anas; Hartoto, Liesbetini; Ani Suryani, Ani Suryani; Nur Atifah, Nur Atifah (2006)
The objective of this research was to examine the aplication of a fed batch cultivation method to produce PHA by Ralstonia eutropha using hydrolysed sago starch as the main substrate. The results showed that a higher formation and accumulation of PHA could be achieved through fed batch cultivation at the dilution rate of 0.1./h. The fed batch cultivation with feeding of substrate containing only hydrolysed sago starch as carbon source resulted the highest specific product yield of 76.54 % and product (PHA) concentration of 3.72 g/L.